2020
DOI: 10.1007/s00411-020-00834-1
|View full text |Cite
|
Sign up to set email alerts
|

The photo-transferred thermoluminescence phenomenon in case of emergency dose assessment

Abstract: A major disadvantage of dose reconstruction by means of thermoluminescence (TL) is the fact that during readout of any TL material exposed to ionizing radiation (i.e., during measuring the glow curve), the radiation-induced signal gets lost. Application of the photo-transferred thermoluminescence phenomenon (PTTL) may offer a solution to this problem. In PTTL, the residual signal that is not destroyed by conventional TL readout (because it comes from deeper electron traps) can be readout through simultaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition, it has been reported that the PTTL signal intensity can be increased by heating the samples during UV exposure and by pre-dose sensitized dosimeters [5,15]. A similar study has been performed in recent years by Wrzesień et al [16]. In this study, PTTL properties of TLD-100 were investigated between 100 and 1000mGy.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…In addition, it has been reported that the PTTL signal intensity can be increased by heating the samples during UV exposure and by pre-dose sensitized dosimeters [5,15]. A similar study has been performed in recent years by Wrzesień et al [16]. In this study, PTTL properties of TLD-100 were investigated between 100 and 1000mGy.…”
Section: Introductionmentioning
confidence: 52%
“…Budzanowski et al [9] reported that the ratio of PTTL intensity to TL intensity reached 17% in their study. Similarly, Wrzesień et al [16] obtained this ratio as 19%. These results are almost compatible with our study.…”
Section: Glow Curves (Tl and Pttl)mentioning
confidence: 76%
See 2 more Smart Citations